1992
DOI: 10.1038/356722a0
|View full text |Cite
|
Sign up to set email alerts
|

Actin-dependent organelle movement in squid axoplasm

Abstract: Studies of organelle movement in axoplasm extruded from the squid giant axon have led to the basic discoveries of microtubule-dependent organelle motility and the characterization of the microtubule-based motor proteins kinesin and cytoplasmic dynein. Rapid organelle movement in higher animal cells, especially in neurons, is considered to be microtubule-based. The role of actin filaments, which are also abundant in axonal cytoplasm, has remained unclear. The inhibition of organelle movement in axoplasm by acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
202
2

Year Published

1992
1992
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 355 publications
(216 citation statements)
references
References 28 publications
12
202
2
Order By: Relevance
“…However, filopodia generally do not contain microtubules, being rich in actin filaments instead (Letourneau and Ressler, 1983;Tosney and Wessells, 1983). Also, there is evidence that membranous organelles can move along actin filaments in axoplasm (Kuznetsov et al, 1992), and a recent report suggested that actin filaments can power the transport of swellings in growth cone filopodia (Sheetz et al, 1990). In occasional optically favorable situations, VEC-DIC microscopy revealed a fiber extending from the living axon into an FLP and even bending or moving from side to side.…”
Section: Resultsmentioning
confidence: 99%
“…However, filopodia generally do not contain microtubules, being rich in actin filaments instead (Letourneau and Ressler, 1983;Tosney and Wessells, 1983). Also, there is evidence that membranous organelles can move along actin filaments in axoplasm (Kuznetsov et al, 1992), and a recent report suggested that actin filaments can power the transport of swellings in growth cone filopodia (Sheetz et al, 1990). In occasional optically favorable situations, VEC-DIC microscopy revealed a fiber extending from the living axon into an FLP and even bending or moving from side to side.…”
Section: Resultsmentioning
confidence: 99%
“…Organelle movement along actin filaments has been demonstrated in algae, 28 squid axoplasm, 29 and in rat neuronal tissue. 30 Moreover, Kuznetsov et al demonstrated in a cell-free system that an individual organelle could move from microtubules directly to microfilaments.…”
Section: Discussionmentioning
confidence: 99%
“…It mediates several essential roles during mitosis (37); together with adhesion molecules, it regulates cell-cell and cell-substrate interactions (38,39) and participates in transmembrane signaling (40), endocytosis (41,42), and secretion (43). Actin filament integrity has been shown to be required for the normal positioning and morphology of the Golgi complex (44).…”
Section: Discussionmentioning
confidence: 99%